Exploring the future: introduction of a new paradigm to examine intergroup experiences - Schäfer, Sarina J. (Frontiers in Social Psychology, 2024)
Intergroup contact theory, as one of the most established research strands in social psychology, has mostly relied on overall measured averages of intergroup contact over larger time spans. Yet, in everyday life, intergroup contact experiences are far more complex: They are sequential and cumulative and may vary on a range of dimensions, such as, for example, their perceived valence. In this article, I introduce a new experimental paradigm, primarily developed as a research manipulation, to examine intergroup contact, manipulated on the unit of single interactions in a video-game setting, which can also be run from a web server, so that participants can join from their home computers. Depending on experimental condition, in a first study, participants rated the perceived quality of multiple positive or negative intergroup interactions with an alien species and intergroup attitudes in a storytelling questionnaire setting (Pilot Study, N = 242). Study 1 implemented these positive and negative interactions in a video game, which was played in the laboratory (N = 44), and examined their effects on the perceived contact quality and intergroup attitudes. Study 2 (N = 64) utilized a web-based version of the video game to test the effects on intergroup attitudes. In all three studies participants in the positive condition evaluated the interactions, as well as the overall outgroup, more positive than participants in the negative condition. Furthermore, Study 1 & 2 explored participants' perception of the virtual environment and previous experiences with video games. The results suggest that specifically developed video games offer new pathways to study intergroup interactions.